AN INVESTIGATION INTO ELEMENTARY SCHOOL STUDENTS' PERCEPTIONS OF BASIC CONCEPTS ABOUT CITIZENSHIP EDUCATION - (:unkn) unknown (HACETTEPE UNIV, 2013)
The purpose of this study was to examine 8 grade students' perceptions of such basic citizenship education concepts as rights, responsibilities, equality, citizenship and sovereignty. Research participants were selected from five different school districts in Istanbul. Qualitative research method was employed to elicit participants' responses to the research questions. A semi-structured interview protocol was used as the main method of data collection. Constant comparison and inductive methods of data analysis were used to analyze data. Research findings showed that students' gender partly impacted their perceptions of the concepts as indicated by female students' perceptions of responsibilities that were far more developed and differentiated than male students'. Most students had a good understanding of rights and responsibilities and knew what to do when their rights were violated. But, some students' perceptions of equality, citizenship and sovereignty were either flawed or incomplete. They had difficulty expressing their meanings, confusing them with other concepts especially with rights, responsibilities and liberty.
Keywords: citizenship education; concepts; social studies; elementary school students; students' perceptions